Frequency of vaginal conditional-pathogenic microflora dependency from age in conditions of normocenosis and disbiosis - Gruzevsky, A. A.; Zyablitsev, S. V.; Chernobrivtsev, P. A. (Journal of Education, Health and Sport, 2017)
298 patients aged 16-64 years were examined who excluded the presence of pathogenic microflora; Polymerase chain reaction (PCR) in real time investigated the biocenosis of the vagina. Depending on the value of the index of opportunistic microflora, the patients were divided into three groups: normocenosis, imbalance I and II degree (dysbiosis). In each group age subgroups were distinguished: from 16 to 25 years, from 26 to 45 years and over 45 years. It is shown that with age and with the increase in the degree of dysbiosis the total bacterial mass and the population of the vagina decreased by lactobacilli. Normocenosis is characterized by a constant occurrence of enterobacteria, an increase in the incidence of candida with age, Eubacterium spp. And Mobiluncus spp. + Corynebacterium spp. In general, Sneathia spp. + Leptotrihia spp. + Fusobacterium spp. And Mycoplasma hominis + genitalium. With the 1st degree disbiosis the incidence of enterobacteria, Candida and Ureaplasma urealiticum + parvum decreased with age, with more frequent occurrence of staphylococci, Megasphaera spp. + Veilonella spp. + Dialister spp. аnd Lachnobacterium spp. + Clostridium spp. The 2nd degree of dysbiosis was characterized by the disappearance of streptococci with age and a decrease in the number of Eubacterium spp. (In patients older than 45 years), an increase in the frequency of obligate anaerobes, especially Mobiluncus spp. + Corynebacterium spp. and Atopobium vaginalis. Mycoplasma hominis + genitalium appeared in the middle age group (26-45 years).